2014
DOI: 10.1002/hup.2421
|View full text |Cite
|
Sign up to set email alerts
|

A review on schizophrenia and relapse—a quest for user‐friendly psychopharmacotherapy

Abstract: Bearing in mind that suboptimal adherence and withdrawal from antipsychotics are an established and unequivocal risk factor for relapse, further investigations are certainly needed to explore user-friendly manner of psychopharmacotherapy to prevent relapse in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 178 publications
(174 reference statements)
0
24
0
Order By: Relevance
“…Some of the caregivers experienced significant stress caused by their ill relatives’ refusal to take medications or to attend follow‐up consultations. Among people with schizophrenia, poor medication adherence is a major issue that brings about negative clinical impacts and relapses , which subsequently intensify caregiver burden . Current evidence has indicated that the use of long‐acting injectable antipsychotics (LAIs) can enhance treatment adherence, reduce relapse rates and improve prognosis in people with schizophrenia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the caregivers experienced significant stress caused by their ill relatives’ refusal to take medications or to attend follow‐up consultations. Among people with schizophrenia, poor medication adherence is a major issue that brings about negative clinical impacts and relapses , which subsequently intensify caregiver burden . Current evidence has indicated that the use of long‐acting injectable antipsychotics (LAIs) can enhance treatment adherence, reduce relapse rates and improve prognosis in people with schizophrenia .…”
Section: Discussionmentioning
confidence: 99%
“…Among people with schizophrenia, poor medication adherence is a major issue that brings about negative clinical impacts and relapses, 18 which subsequently intensify caregiver burden. 19 Current evidence has indicated that the use of long-acting injectable antipsychotics (LAIs) can enhance treatment adherence, reduce relapse rates and improve prognosis in people with schizophrenia. 20,21 Moreover, a recent post hoc analysis revealed that, for people on prior oral antipsychotics after switching to LAIs, caregiver burden was significantly alleviated, with reductions in workdays missed, leisure time affected and time spent in caregiving.…”
Section: Stress and Burden Faced By Family Caregiversmentioning
confidence: 99%
“…There were four patients who were successfully withdrawn from antipsychotic treatment. Compared with those who needed continuous antipsychotic treatment in the same unit (n¼ 51), they were significantly older (77.078.6 versus 56.0 712.1 y.o., p o0.01) and had been treated with a fewer number of total psychotropics at baseline (1.50 71.00 versus 4.947 1.93 agents, p o0.001) by Mann-Whitney U-Test; details were summarized elsewhere (Suzuki, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Many difficult patients were successful to be treated with a twice-daily or even single-night dosing (Suzuki et al, 2005); which would be important in the interest of consumers for convenience as poor adherence is a well-established factor for relapse in schizophrenia (Suzuki et al, 2014) and plausibly, patients generally prefer once daily dosing to more complex schedules (Witticke et al, 2012). This may be also positive for caregivers and nursing staff by reducing the burden of giving the medicines frequently on a regular basis.…”
Section: Discussionmentioning
confidence: 97%
“…Non-adherence to antipsychotic treatment has been associated with relapses, poorer life satisfaction, substance-and alcohol abuse and even suicides 18,19 . Besides inducing hazards for the patient, these outcomes may www.nature.com/scientificreports www.nature.com/scientificreports/ also stress parents or other caregivers significantly 20 . The burden on parents of the patient with the disorder is often presented as informal caregiving, i.e.…”
mentioning
confidence: 99%